2020
DOI: 10.1096/fj.201902751r
|View full text |Cite
|
Sign up to set email alerts
|

HUWE1 promotes EGFR ubiquitination and degradation to protect against renal tubulointerstitial fibrosis

Abstract: Injury of renal tubular epithelial cells is a key feature of the pathogenicity associated with tubulointerstitial fibrosis and other kidney diseases. HUWE1, an E3 ubiquitin ligase, acts by participating in ubiquitination and degradation of its target proteins. However, the detailed mechanisms by which HUWE1 might regulate fibrosis in renal tubular epithelial cells have not been established. Here, the possible regulation of renal tubulointerstitial fibrosis by HUWE1 was investigated by examining the expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Interestingly, ZC3H15 positively regulated the protein ability of EGFR. Given that EGFR can be ubiquitinated by E3 ligases, meanwhile, we found that the ubiquitination level of EGFR was reduced in the existence of ZC3H15 [ 40 , 41 ]. It is noteworthy that, ZC3H15 has no Ring finger domain or HECT domain, which is crucial for targeting protein degradation [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, ZC3H15 positively regulated the protein ability of EGFR. Given that EGFR can be ubiquitinated by E3 ligases, meanwhile, we found that the ubiquitination level of EGFR was reduced in the existence of ZC3H15 [ 40 , 41 ]. It is noteworthy that, ZC3H15 has no Ring finger domain or HECT domain, which is crucial for targeting protein degradation [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis showed that AKT1, EGFR, and TNF may be potential targets for FSGD in the treatment of CRF, and the PPI network indicated that AKT1 was one of the central genes related to 40 highly valuable targets and is closely related to fibrosis, and it may be a new target for CRF ( Lin et al, 2020 ). AKT1 can promote EGFR ubiquitination and degradation to prevent renal intertubule fibrosis ( Zhu et al, 2020 ). Neutralizing inflammatory cytokines (TNF) can reduce the level of FGF23 in animal models of chronic kidney disease (CKD) and high levels of FGF23 are associated with increased cardiovascular morbidity and mortality in patients with CKD ( Egli-Spichtig et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Obstructive nephropathy activates the EGFR signaling pathway, which regulates renal cell growth, survival, and proliferation. Overexpression of EGFR could increase the expression and activation of TGF- β 1 and the release of inflammatory cytokines like IL-6 [ 44 ]. IL-6 is a pleiotropic cytokine with a wide range of functions.…”
Section: Discussionmentioning
confidence: 99%